(untitled) (Journal of Teleological Science, 2022)
We must begin this article with the justification of its title: the term télos comes from Greek and has, among several meanings, that of being the point towards which a reality moves, the purpose or objective. The reality on which this study is focused is the Socio-Educational System, with a case study of the Centro Socioeducativo de Juiz de Fora (CSEJF) and the semiliberty units. However, before delving into the specific issue of the aforementioned county, it is worthwhile to look at the implementation and reality of social-education in the state of Minas Gerais and, in particular, in the city that is the object of this study.